Frequency and Motives of Sharing Dreams: Personality Correlates. (June 2021) - Graf, Daniel; Schredl, Michael; Göritz, Anja S.
Abstract: Sharing dreams is a common practice and several motives like emotional relief, entertainment, understanding the dream for doing so have been identified. However, little is known about factors associated with these motives. The present online survey ( N  = 1585) investigated the associations of the Big5 personality factors with motives for sharing a specific dream. Findings indicate that neurotic people tend to share dreams for the purpose of emotional relief, extraverted people for entertainment and self-expression, persons with high openness to experience are interested in the meaning of the dream and what other people think about it. In addition, the emotional tone of the shared dream showed a strong effect: positive dreams are shared for entertainment purposes and to appear more interesting and negative dreams more often for emotional relief. Longitudinal diary studies would be desirable to analyze dream sharing situations in a more detailed way, e.g., the interaction with the person the dream is shared with. Graphical abstract: Relative contributions of different variables to the six dream sharing motives in this study. Unlabelled Image Highlights: Younger age, dream recall, and nightmare frequency are associated with dream sharing. Personality shows small yet significant associations with dream sharing frequency. Neuroticism was associated with the dream sharing motive of emotional relief. Openness was associated with the motive of understanding the dream. Emotional dreams are more likely to be shared than mundane ones.